Appropriately delayed flooding before rice transplanting increases net ecosystem economic benefit in the winter green manure-rice rotation system - Zhengbo Ma; Rongyan Bu; Guopeng Zhou; Haoran Fu; Jinxin Sun; Ting Liang; Cheng Cai; Danna Chang; Qingxu Ma; Ji Wu; David R. Chadwick; Davey L. Jones; et al. (Resources, Environment and Sustainability)
In southern China, co-incorporating winter green manure and rice straw has proven to be a practical and economically viable strategy that enhances soil carbon (C) sequestration and agricultural productivity in rice paddies. However, the issue of how to control the greenhouse gas (GHG) emissions in paddy fields owing to the incorporation of substantial organic matter remains a bottleneck. A 2-year field experiment was conducted, which included five treatments: conventional water management with no residue (CK) and with co-incorporation of green manure and rice straw (GM+Rs), delayed flooding by 5, 10, and 15 days after the co-incorporation of green manure and rice straw (GM+Rs-DW5, GM+Rs-DW10, and GM+Rs-DW15) before transplanting rice seedlings. The delayed flooding treatments reduced the 2-year average CH4 emissions by 40.9%–60.8% compared with GM+Rs. The delayed flooding inhibited the growth of methanogens and CH4 emissions, which was linked to a reduction of dissolved organic carbon (DOC) concentration in surface water. The lowest C footprint (4.05 t CO2-eq ha−1) as well as the yield-scaled C footprint (0.6 kg CO2-eq kg−1) were observed in the GM+Rs-DW10 treatment, both even lower than those in CK (15.11 t CO2-eq ha−1and 2.1 kg CO2-eq kg−1). Moreover, the GM+Rs-DW10 treatment led to an increase in net ecosystem economic benefit (NEEB) of 3750 and 2870 CNY ha−1 than CK and GM+Rs over a 2-year period. Collectively, delayed flooding with green manure and rice straw incorporation is conducive to achieving high NEEB and low risk of GHG emissions. This finding provides important and novel insights for eco-efficient rice production.